2017
DOI: 10.1111/rda.12985
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐like growth factor I enhances the developmental competence of yak embryos by modulating aquaporin 3

Abstract: The objective of our present study was to determine the effects of insulin-like growth factor I (IGF-I) on the development of yak (Bos grunniens) embryos after cumulus-oocyte complex (COC) vitrification and warming followed by in vitro fertilization (IVF). In Experiment 1, the yak COCs underwent vitrification and then IVF. Embryos were incubated in synthetic oviductal fluid (SOF) supplemented with four concentrations (0, 50, 100 and 200 ng/ml) of IGF-I, while the yak COCs without vitrification or IGF-I supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The composition of in vitro maturation media has strong impact on oocyte quality and cryotolerance. In this regard, supplementation of maturation and culture media with insulin-like growth factor I (IGF-I) stimulates oocyte maturation and promotes blastocyst development in several species (Kocyigit and Cevik, 2015; Pan et al, 2015; Arat et al, 2016; Chen et al, 2017). In pigs, although IGF-I has been reported to promote the synthesis of hyaluronic acid and the expansion of cumulus cells (Nemcova et al, 2007), its role in IVM remains unclear and has yield inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of in vitro maturation media has strong impact on oocyte quality and cryotolerance. In this regard, supplementation of maturation and culture media with insulin-like growth factor I (IGF-I) stimulates oocyte maturation and promotes blastocyst development in several species (Kocyigit and Cevik, 2015; Pan et al, 2015; Arat et al, 2016; Chen et al, 2017). In pigs, although IGF-I has been reported to promote the synthesis of hyaluronic acid and the expansion of cumulus cells (Nemcova et al, 2007), its role in IVM remains unclear and has yield inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Cys is a critical component amino acid of glutathione (GSH), which plays an important role in protecting from the toxic effect of oxidative damage (Meister 1983). EGF and IGF-1 are involved in regulating cell proliferation and apoptosis (Paria and Dey 1990;Wasielak and Bogacki 2007;Chen et al 2017). Positive effects on oocyte maturation and/or embryonic development have been observed if a single or different combination of Cys, EGF and IGF-1 concentrations in IVM, IVF and IVC media is optimal in cattle (Ali et al 2003;Sirisathien et al 2003;Neira et al 2010;Nabenishi et al 2012), pig (Choe et al 2010;Lott et al 2011), sheep (Shabankareh and Zandi 2010), buffalo (Pawshe et al 1998), human (Yu et al 2012), mouse (Toori et al 2014); cat (Thongkittidilok et al 2015), goat (Conceicao et al 2016;Zhou et al 2016), canine (Sato et al 2018) and yak (Pan et al 2015;Chen et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The experiment contained eight groups: Cys, IGF-1, EGF, IGF-1 + EGF, IGF-1 + Cys, EGF + Cys, IGF-1 + EGF + Cys, and control. These concentrations were chosen because they had previously been shown to be the most effective dosage for IVM and IVC in some studies (Shabankareh and Zandi 2010;Lott et al 2011;Chen et al 2017)…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…This may indicate a potential regulatory mechanism between miR-152 and the IGF system during oocyte development. Several studies reported that IGF-1 is involved in the regulation of follicular, oocyte, and embryonic development and the proliferation of follicular cells [38][39][40]. A signi cant correlation between IGF1 expression and blastocyst formation has been observed in mice [41].…”
Section: Discussionmentioning
confidence: 99%